2019
DOI: 10.1007/s00339-019-2885-1
|View full text |Cite
|
Sign up to set email alerts
|

Expected X-ray dose rates resulting from industrial ultrafast laser applications

Abstract: An analytical model is presented, which allows estimating the expected dose rates resulting from X-ray emission from ultrashort-pulse laser-produced plasma under industrial conditions. The model is based on the calculation of the Bremsstrahlung spectrum in the X-ray region between about 5 keV and 50 keV, which is created by the hot electrons in the plasma. The model was calibrated with both spectral and dose rate measurements. The scaling of the hot-electron temperature and the fraction of hot electrons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 30 publications
(83 reference statements)
4
52
0
Order By: Relevance
“…The monitored Bremsstrahlung spectra represent qualitatively the energy distribution of the X-ray photon flux at 100 mm distance and can be approximated by a Maxwell–Boltzmann distribution [ 9 , 12 ] according to where k B represents the Boltzmann constant, T e is the electron temperature, and E is the energy of the emitted X-ray photons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitored Bremsstrahlung spectra represent qualitatively the energy distribution of the X-ray photon flux at 100 mm distance and can be approximated by a Maxwell–Boltzmann distribution [ 9 , 12 ] according to where k B represents the Boltzmann constant, T e is the electron temperature, and E is the energy of the emitted X-ray photons.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent works have shown that the X-ray photon emission increases proportionally with higher average laser power, and actual X-ray emission dose rates can cause serious health risks for the laser operators [ 9 , 10 , 11 , 12 , 13 , 14 ]. In particular, this is the case when high-pulse repetition frequency lasers will be used in materials ablation as the X-ray emission per pulse can accumulate to harmful X-ray photon dose over time.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism generating X-rays during ultrafast laser interaction with materials has been described elsewhere [ 3 , 4 , 8 ]. Under experimental conditions, high-kinetic-energy electrons would directly collide against electrons in atoms inner shell orbitals, resulting in the emission of characteristic lines for e.g., k-α, k-β line emissions along with a bremsstrahlung mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been demonstrated that ultrashort laser machining can be accompanied with an X-ray radiation at high repetition rates, if the peak intensity exceeds 10 13 W/cm 2 [ 3 , 4 , 5 , 6 ]. Industrial laser sources used for materials processing typically have pulse durations in the range of pico- to femtoseconds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation